Gabapentin as Pre-Emptive Analgesic Agent Given To Abdominal Hysterectomy Patients for Post-Operative Analgesia - Mohd. Abdul Moiz; Sunil Bablu Pulla (Academia Anesthesiologica International, 2020)
Background: Pain after hysterectomy is often multifactorial from various causes. Pain occurs from the incision site, deeper visceral systems, and pain in action, such as through straining, coughing, or mobilisation, which can be serious. The objective is to evaluate whether Gabapentin when given orally preoperatively at a dose of 300 mg affects postoperative pain and analgesic requirements in patients undergoing total abdominal hysterectomy under spinal anaesthesia. Subjects and Methods: This is a prospective, randomised, double-blind, placebo-controlled sample. This research was performed on a total of 60 patients who underwent an elective abdominal hysterectomy at our institute. Patients were randomly assigned to two groups: Group G (Gabapentin Group) and Group P (Placebo Group). Group G patients received Gabapentin 300 mg orally   and Group P patients received placebo capsules with sips of water two hours before the operation. Period from spinal anaesthesia to the first analgesic (T) requirement, a complete analgesic requirement in the first 24 hours, visual analogue scale (VAS) rest and activity ratings, Ramsay sedation score, drug side effects such as somnolence, dizziness, confusion, nausea, vomiting were reported in 0,2,4,6,12 hours postoperatively. Results: When administered preoperatively, a single oral dose of Gabapentin 300 mg lowers postoperative pain and overall tramadol intake    in the abdominal anaesthesia patients. For Gabapentin usage, sedation was the most important side effect. Gabapentin should also be used as    a supplement for the management of postoperative pain. Conclusion: This study shows that a single oral dosage of 300mg of gabapentin as pre-operatively administered decreases the post-operative discomfort and overall utilisation of tramadol in abdominal hysterectomy patients with spinal anaesthesia.